Efektivitas Warm Water Footbath dan Aromatherapy Terhadap Kualitas Tidur Lansia: Systematic Review - Alifah Ade Nuary; Endang Triyanto (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2022)
Background: The aging process in the elderly affects the quality of sleep. More than 50 percent of the elderly meet sleep disorders ranging from mild to severe degrees. Various studies have been carried out to improve the quality of sleep in the elderly, but it is not yet known which is the most effective.Objective: To determine the effectiveness of warm water footbath and aromatherapy on the sleep quality of the elderly.Method: This research includes a systematic review. Search articles using the keywords "footbath", "sleep quality", "elderly" and "aromatherapy", "sleep quality", and "elderly" in the Cochrane database, ProQuest, PubMed, Science Direct, and Google Scholar. Article screening uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses method. Assessment of the quality of articles using a questionnaire guide The Joanna Briggs Institute.Outcome: Obtained three articles related to warm water footbath intervention and 2 related to aromatherapy. Both affect on improving the sleep quality of the elderly, but a warm water footbath is considered more effective than aromatherapy.Conclusion: Warm water foot bath therapy is more effective than aromatherapy in improving the sleep quality of the elderly.ABSTRAKLatar belakang: Proses penuaan pada orang lanjut usia (lansia) berpengaruh terhadap kualitas tidur. Lebih dari 50 persen lansia mengalami gangguan tidur, mulai dari derajat ringan hingga berat. Berbagai penelitian terkait intervensi yang dapat meningkatkan kualitas tidur lansia telah dilakukan, di antaranya adalah warm water footbath dan aromaterapi. Belum diketahui mana yang paling efektif dari kedua intervensi tersebut.Tujuan: Tujuan penelitian ini untuk mengetahui efektivitas terapi warm water footbath dan aromatherapy terhadap kualitas tidur lansia.Metode: Penelitian ini termasuk systematic review. Pencarian artikel menggunakan kata kunci “footbath”, “sleep quality”, “elderly” dan “aromatherapy”, “sleep quality”, “elderly” pada database Cochrane, ProQuest, PubMed, Science Direct, dan Google Scholar. Skrining artikel menggunakan metode preferred reporting items for systematic reviews and meta-analyses. Penilaian kualitas artikel menggunakan panduan kuesioner The Joanna Briggs Institute.Hasil: Diperoleh tiga artikel terkait intervensi warm water footbath dan 2 artikel terkait aromatherapy. Keduanya berpengaruh terhadap peningkatan kualitas tidur lansia, tetapi a warm water footbath dinilai lebih efektif dibandingkan aromatherapy.Simpulan: Terapi warm water footbath lebih efektif dibandingkan aromatherapy dalam meningkatkan kualitas tidur lansia.